Effect of Transcutaneous Spinal Cord Stimulation on Spasticity, Mobility, Pain and Sleep in Community Dwelling Individuals Post-Stroke - A single case withdrawal design - Belinda Chenery 1975- (2019)
Effective treatment modalities for alleviating spasticity and pain and enhancing mobility and sleep are limited post-stroke. Some evidence suggests that techniques of transcutaneous spinal cord stimulation (tSCS) may be beneficial. However, these are typically small pretest-posttest studies with high risk of bias. To date, there are no studies that evaluate the effects of tSCS in stroke. The aim of the current study was to evaluate the effects of daily home-treatment with tSCS on spasticity, mobility, pain and sleep in community dwelling individuals post-stroke. Four cases were included in a single-subject withdrawal research design comprised of two alternating baseline and intervention phases (ABAB). Each phase consisted of three measurement sessions. Clinical, biomechanical and self-report data were collected and analysed with visual and statistical techniques, suitable for single-subject design. The intervention consisted of daily home application of tSCS for three weeks. Treatment efficacy was disparate between participants. For one out of the four cases, the results revealed large effect sizes for spasticity, mobility, pain and sleep when using tSCS the first time. Maintenance of effect size from the first baseline to second intervention phase was statistically significant for mobility, pain and sleep. In the other three cases, apart from an improvement on two occasions for mobility measures, there were no improvements. Repetition of a positive effect size was not demonstrated in any case. The results of the study indicate that tSCS may be a useful tool in post-stroke rehabilitation for alleviating spasticity and pain and enhancing mobility and sleep in some community dwelling individuals post-stroke. This inexpensive, non-invasive and easily accessible home-treatment method may be a suitable tool for some individuals. Icelandic Physiotherapy Association National University Hospital of Iceland